Structure, characteristics, and simulation of monsoon low‐pressure systems in CFSv2 coupled model. Issue 8 (17th August 2017) - Srivastava, Ankur; Rao, Suryachandra A.; Rao, D. Nagarjuna; George, Gibies; Pradhan, Maheswar
Abstract: Indian Summer Monsoon (ISM) synoptic scale systems (low‐pressure systems, LPS) are known to produce increased rainfall over central India (CI). Fidelity of the Climate Forecast System version 2 (CFSv2) at simulating the LPS and their characteristics is evaluated in this study using a feature tracking algorithm. The model is able to reproduce the clustering of LPS by monsoon intraseasonal oscillations and the associated precipitation over eastern‐central India. It is found that mean biases in circulation and moisture stem from cold sea surface temperature (SST) bias in the model which results in weak LPS linked rainfall events over central India. Two sensitivity experiments were carried out to study the effect of coupled dynamics of tropical basins on LPS. Suppression of active dynamics of the tropical Indian Ocean in CFSv2 causes a reduction in cold SST bias and enhanced cyclogenesis in the northern Bay of Bengal. The reduced low‐level anticyclonic bias and enhanced moisture availability result in a better simulation of LPS structure, and associated precipitation over CI. Suppression of active ocean dynamics in tropical Pacific Ocean causes a perennial El‐Niño type bias which restricts LPS propagation over the Indian landmass, possibly due to time‐mean subsidence induced by remote El‐Niño forcing. Sensitivity experiments indicate the need for improvements in the representation of tropical Indian Ocean coupled dynamics as well as convective parameterization schemes in the model for subsequent improvements in the simulation of ISM at various time scales. Key Points: Monsoon low‐pressure systems Ocean‐atmosphere coupled dynamics Tracking algorithm